Preliminary investigation of tensile properties of welded type I collagen to be used as surgical sealant - Ghazali, M.; Kadri, Nahrizul Adib (Academic Journals, 2011)
Type I collagen has been identified as the most abundant protein in the human body, and it has been used extensively in the healthcare industry as a biomaterial for the purposes of soft tissue repair, tissue engineering and many other areas. The aim of this study was to research the mechanical tensile strength of type I collagen when welded together for possible use as a sealant biomaterial for surgical closure. Sheets of type I collagen from calf skin were prepared using collagen granules and a 1.6 M acetic solution. The sheets were cut into smaller pieces and welded together at different widths using a magnetic heat plate. Mechanical tensile properties were subsequently determined using a tensiometer. A set of six parameters were selected as the variables of choice for the purpose of analyzing the mechanical properties, namely, the tensile stress and tensile strain at the point of failure, the maximum load that was applied to the collagen sample and the physical dimensions of each of the collagen samples. It was found that only the tensile strain at failure point is significantly different (P < 0.01) between the different groups of collagen samples. However, a conclusive decision could not be made based on this finding alone, and further investigations are warranted. Â© 2011 Academic Journals.